Anisotropic large diamagnetism in Dirac semimetals ZrTe5and HfTe5 - Singh, Sukriti; Kumar, Nitesh; Roychowdhury, Subhajit; Shekhar, Chandra; Felser, Claudia (Journal of Physics: Condensed Matter, 2022)
Dirac semimetals, e.g., ZrTe5 and HfTe5, have been widely investigated and have exhibited various exotic physical properties. Nevertheless, several properties of these compounds, including diamagnetism, are still unclear. In this study, we measured the temperature- and field-dependent diamagnetism of ZrTe5 and HfTe5 along all three crystallographic axes (a-, b-, and c-axis). The temperature-dependent magnetization shows an anomaly, which is a characteristic of Dirac crossing. Diamagnetic signal reaches the highest value of 17.3 × 10-4 emu mol-1 Oe-1 along the van der Waals layers, i.e., the b-axis. However, the diamagnetism remains temperature-independent along the other two axes. The field-dependent diamagnetic signal grows linearly without any sign of saturation and maintains a large value along the b-axis. Interestingly, the observed diamagnetism is anisotropic like other physical properties of these compounds and is strongly related to the effective mass, indicating the dominating contribution of orbital diamagnetism in Dirac semimetals induced by interband effects. ZrTe5 and HfTe5 show one of the largest diamagnetic value among previously reported state-of-the-art topological semimetals. Our present study adds another important experimental aspect to characterize nodal crossing and search for other topological materials with large magnetic susceptibility.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anisotropy; diamagnetism; Dirac semimetal; effective mass